(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2020)
The fatty acid analysis and biological activity of n-hexane, dichloromethane, ethyl acetate and methanol extracts of Nyctanthes arbor-tristis L. flowers are reported. Five fatty acids namely palmitic (44.15%), stearic (19.34%), arachidic (15.06%), behenic (9.77%) and lignoceric (11.69%) acids were identified. From cytotoxicity test, the LC50 values (the median lethal concentration) for n-hexane, dichloromethane, ethyl acetate and methanol extracts as well as for standard vincristine sulphate were found 7.05, 4.67, 3.14, 5.53 and 0.50 μg/ml, respectively. Antibacterial activity results of different extracts were compared with standard antibiotic ciprofloxacin and tetracycline by measuring the zone of inhibition diameter in millimeter. The dichloromethane and ethyl acetate extracts showed significant antibacterial activity. From antioxidant activity test, IC50 values (50% inhibitory concentration) of n-hexane, dichloromethane, ethyl acetate, methanol extracts and ascorbic acid were found to be 291.92 mg/ml, 45.74 μg/ml, 21.86 μg/ml, 64.30 μg/ml and 3.98 μg/ml, respectively. Bangladesh J. Sci. Ind. Res.55(3), 207-214, 2020